Optimization method of synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process

By introducing synchronous ultrasonic field and single-factor control experimental optimization process parameters in the zinc electrodeposition process, the problem of high oxygen overpotential of the anode of Pb-Ag alloy is solved, and the effect of reducing power consumption and cost and suppressing anode corrosion is achieved.

CN119433631APending Publication Date: 2025-02-14ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411368620.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing zinc electrostatic deposition process, the oxygen evolution overpotential of the Pb-Ag alloy anode is relatively high, resulting in high power consumption, increased cost, and fast anode corrosion rate.

Method used

By introducing a synchronous ultrasonic field into the zinc electrodeposition process, the electrodeposition process is regulated, the oxygen evolution overpotential of the anode is reduced, and the process parameters are optimized through single-factor control experiments, and the correlation relationship between variable factors and optimization effects is established.

Benefits of technology

It significantly reduces the oxygen evolution overpotential of the anode, reduces the power consumption and cost during zinc electrostatic accumulation, and effectively suppresses the corrosion of the anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433631A_ABST
    Figure CN119433631A_ABST
Patent Text Reader

Abstract

The invention discloses an optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process. The method comprises the steps that a Pb-Ag alloy serves as an electrode, and a zinc electrodeposition electrolytic bath and an LSV testing electrolytic bath are built respectively; respectively electrifying the zinc electrodeposition electrolytic bath and the LSV test electrolytic bath for electrolysis, and applying a synchronous ultrasonic field to obtain an anode LSV curve; after electrolysis is finished, the anode is recycled, an electrodeposition oxidation layer film of the recycled anode is reserved, and an LSV curve of the electrodeposition oxidation layer film is obtained again; and repeating the steps to perform single-factor variable optimization on the zinc electrodeposition process parameters to obtain the optimal process conditions. According to the method, through a single-factor control experiment on variable factors in the zinc electrodeposition process, a correlation relation between each variable factor and an optimization effect is established by utilizing oxygen evolution overpotential and the ion concentration of an electrodeposition electrolyte, so that the optimal process condition is obtained in a targeted manner; the problems that in the prior art, in the zinc electrodeposition process of an anode, the oxygen evolution overpotential of the anode is high, the corrosion rate of lead and silver is high, and the zinc electrodeposition cost is increased are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for optimizing a zinc electrowinning process, in particular to a method for optimizing a synchronous ultrasonic field low oxygen evolution overpotential zinc electrowinning process, and belongs to the technical field of wet smelting. Background Art

[0002] Zinc is an indispensable product in the national economy, mainly used for corrosion protection, batteries, alloys, etc. Zinc smelting methods include pyrometallurgy and hydrometallurgy, of which hydrometallurgy accounts for 80% of the production capacity. The hydrometallurgy process includes "zinc roasting, roasting sand, leaching, leachate purification, zinc electrolysis" and other processes. The production cost of hydrometallurgy is mainly power consumption, which is about 60% of the total cost, and the DC power consumption of zinc electrolysis accounts for about 80% of the total power consumption of hydrometallurgy. The main reasons for its high energy consumption include: (1) the oxygen evolution catalytic activity of Pb-Ag alloy anode is general and its oxygen evolution overpotential is high; (2) in the zinc electrolysis process, Pb-Ag alloy participates in the electrochemical reaction as the anode, and there are film-forming reaction and corrosion reaction at the same time as the oxygen evolution reaction. This series of complex reactions also increases the overpotential of the anode; (3) during the zinc electrolysis process, the film-forming reaction forms a PbO2 oxide layer on the surface of the Pb-Ag alloy, which inhibits the oxygen evolution catalytic activity of silver in zinc electrolysis.

[0003] From the analysis of zinc electrowinning process, it can be seen that the Pb-Ag alloy anode still has a high overpotential, which causes the cell voltage to be too high, so that the zinc electrowinning process consumes a lot of energy. Therefore, reducing the energy consumption in the zinc electrolysis process has attracted the attention of many researchers and enterprises. At present, the methods to reduce the energy consumption in the zinc electrolysis process mainly include: (1) using lead as the matrix to prepare lead alloy anodes with excellent conductivity, high electrocatalytic activity and good stability, such as binary alloys such as Pb-Ag, Pb-Ca, Pb-Sb, Pb-Sn and ternary alloys such as Pb-Ca-Sn and Pb-Ag-Nd; (2) using other corrosion-resistant and low-cost metals instead of lead as the matrix, and coating the surface of the matrix with a layer of high corrosion resistance and high electrocatalytic activity, such as titanium-based coating materials, stainless steel-based inert anode materials, aluminum-based inert anode materials, etc.; (3) purifying the electrolyte to reduce the influence of impurity ions on the anode reaction and cathode zinc deposition reaction in the zinc electrolysis process, such as reducing the concentration of manganese, chlorine and fluorine ions; (4) adding an appropriate amount of additives to the electrolyte to reduce the harm of impurities and improve the current efficiency, such as gelatin, strontium carbonate, etc.

[0004] However, the above methods all have the problems of excessive energy consumption and high cost. In the actual zinc smelting process, in order to stabilize production capacity and reduce production costs, the electrolytic conditions are basically kept constant, but the cost of preparing other alloy anodes will increase sharply. The concentration of impurity ions in the electrolyte depends on the previous leaching process. Therefore, the market urgently needs a zinc electrolytic process that can ensure a low concentration of impurity ions in the electrolyte and save energy and reduce costs. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides an optimization method for a synchronous ultrasonic field low oxygen evolution overpotential zinc electrowinning process. The optimization method obtains the LSV curve of the Pb-Ag anode by conducting a single factor control experiment on each variable factor in the zinc electrowinning process, and regulates the electrowinning process by adding an additional synchronous ultrasonic field, and then establishes a correlation relationship between each variable factor and the optimization effect through the oxygen evolution overpotential and the ion concentration of the electrowinning electrolyte, effectively solving the problems of the high anode oxygen evolution overpotential, fast corrosion rate of lead and silver, and increased zinc electrowinning cost in the prior art.

[0006] In order to achieve the above technical objectives, the present invention provides a method for optimizing a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process, the process of which comprises:

[0007] Step S1, using Pb-Ag alloy as electrodes, respectively building a zinc electrowinning electrolytic cell and an LSV test electrolytic cell;

[0008] Step S2, respectively energizing and electrolyzing the zinc electrolytic cell and the LSV test electrolytic cell and applying a synchronous ultrasonic field to obtain an anode LSV curve;

[0009] Step S3, after the zinc electrolytic deposition is completed, the anode is recovered, the electrolytic oxide layer film of the recovered anode is retained and its LSV curve is obtained again;

[0010] Step S4, repeating steps S1 to S3 to perform single factor variable optimization on zinc electrowinning process parameters to obtain the best process conditions;

[0011] The zinc electrolytic cell comprises: a solution containing Zn2+ as an electrolytic solution, a Pb-Ag alloy anode, and an Al cathode;

[0012] The LSV test electrolytic cell comprises: sulfuric acid electrolyte, Pb-Ag alloy as working electrode, platinum sheet electrode as auxiliary electrode, and mercurous sulfate electrode as reference electrode.

[0013] As a preferred solution, the electrolytic solution comprises 100-150 g / L sulfuric acid and 30-70 g / L Zn 2+ .

[0014] As a preferred solution, the Pb-Ag alloy needs to be pretreated, and the process is: the Pb-Ag alloy is polished flat with 600 mesh and 1200 mesh sandpaper in turn, and then ultrasonically degreased and cleaned and dried to obtain the alloy.

[0015] As a preferred solution, the power of the synchronous ultrasonic field is 100-800 W, and the frequency is 20-60 kHz.

[0016] As a preferred solution, the conditions of the zinc electrowinning process are: the current density is 40-60 mA / cm 2 , the temperature is 20 ~ 50 ℃.

[0017] As a preferred solution, the anode recovery process is as follows: the anode that has completed zinc electrowinning is rinsed with distilled water and anhydrous ethanol for 2 to 5 times in sequence, and then vacuum dried to obtain the anode.

[0018] As a preferred solution, the test process of the recovery anode LSV curve is: using a three-electrode system and 100-150 g / L sulfuric acid as the electrolyte to perform an electrocatalytic oxygen evolution test.

[0019] As a preferred solution, the variable factors for optimizing the zinc electrowinning process parameters include: electrowinning temperature, electrowinning time, ultrasonic field and current density.

[0020] As a preferred solution, before optimizing the zinc electrowinning process parameters, it is also necessary to test the ion concentration of the zinc electrowinning electrolyte to obtain the lead and silver ion concentrations.

[0021] As a preferred solution, the zinc electrowinning process parameter optimization process is to statistically analyze the LSV curves and ion concentrations of the zinc electrowinning electrolyte obtained under each single factor variable experiment, and establish a correlation between the optimization effect and each variable factor through the two.

[0022] As a preferred solution, the decrease in the oxygen evolution overpotential is positively correlated with the optimization effect; and the ion concentration is negatively correlated with the optimization effect.

[0023] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:

[0024] 1) The optimization method provided by the present invention obtains the LSV curve of the Pb-Ag anode through a single-factor control experiment on each variable factor in the zinc electrowinning process, and regulates the electrowinning process by adding an additional synchronous ultrasonic field, and then establishes a correlation relationship between each variable factor and the optimization effect through the oxygen evolution overpotential and the ion concentration of the electrowinning electrolyte, which effectively solves the problems of the high anode oxygen evolution overpotential, fast corrosion rate of lead and silver, and increased zinc electrowinning cost in the prior art during the zinc electrowinning process.

[0025] 2) In the technical solution provided by the present invention, the synchronous ultrasonic field used can, on the one hand, accelerate the rate of oxygen separation at the anode during electrolysis, reduce the solution resistance, and thus significantly reduce the oxygen evolution overpotential; on the other hand, it can also regulate the growth of PbO2 on the anode surface, inhibit silver corrosion, increase the active sites of silver on the anode surface, enhance the electrocatalytic activity of the anode, and thus further reduce the oxygen evolution overpotential. In addition, it was found through testing that the concentration of anode metal ions in the electrolyte after zinc electrolysis under the application of an ultrasonic field decreased significantly, which also shows that the ultrasonic field can effectively inhibit anode corrosion.

[0026] 3) In the technical solution provided by the present invention, the zinc electrowinning process obtained based on the optimization method has the advantages of low cost, stable process and simple flow. After testing, compared with the prior art, the linear voltammetry (LSV) method is used to measure the zinc electrowinning process at 50 mA / cm 2 The oxygen evolution overpotential under the condition of electrolysis decreased by about 105mV. After 5h of electrolysis, the anode was subjected to LSV test, and its oxygen evolution overpotential decreased by 125mV. Furthermore, the ion concentration of the electrolyte was tested by ICP after 5h of electrolysis, and its Ag ion concentration was only half of that in the prior art. By testing the voltage change curve of the zinc electrolysis cell, when the curve tended to be stable, the cell voltage also decreased by 50mV compared with the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A diagram of a device for simulating zinc electrowinning testing in a test of an embodiment of the present invention;

[0028] Figure 2 The LSV curves of the Pb-Ag anode in the electrochemical test electrolyte when the ultrasonic field is applied and when the ultrasonic field is not applied in Examples 1, 2 and 3 of the present invention;

[0029] Figure 3 The SEM image and EDS surface scan data of the Pb-Ag alloy oxide film layer after zinc electrowinning for 5 hours in Example 4 of the present invention;

[0030] Figure 4 This is an LSV curve of the Pb-Ag alloy oxide film in the electrochemical test electrolyte after zinc electrowinning for 5 hours in Example 4 of the present invention;

[0031] Figure 5 The cell voltage variation curve diagram during zinc electrowinning for 5 hours in Example 5 of the present invention;

[0032] Figure 6 This is a SEM image of the cathode product zinc after zinc electrowinning for 5 hours in Example 5 of the present invention;

[0033] Figure 6 (a) is the SEM image of zinc crystals obtained by applying synchronous ultrasonic field. Figure 6(b) is the SEM image of zinc crystals obtained without applying synchronous ultrasonic field. DETAILED DESCRIPTION

[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0038] In order to better illustrate the characteristics of the optimization method of the present invention, the most original zinc electrowinning process was optimized. The process conditions were that the zinc electrowinning electrolyte solution was 150 g / L H2SO4 and 50 g / L Zn 2+ The electrolytic cell adopts a conventional experimental-grade electrolytic cell with a capacity of 200 mL and is actually filled with 150 mL of electrolyte; the temperature range of the zinc electrowinning process is 20°C to 50°C, and the current density range of the zinc electrowinning process is 40 to 60 mA / cm 2 .

[0039] The zinc electrowinning test device in the embodiment of the present invention is shown in FIG. Figure 1 As shown, in order to better illustrate the advantages of the optimization method provided by the present invention, the most common Pb-Ag alloy in the electrowinning process is used as the anode, and its Ag content is 1wt.%; the anodes used in the following embodiments and comparative examples are all pretreated, and the process is as follows: the cut 20mm×20mm×2mm Pb-Ag alloy is polished to a bright finish using 600-mesh and 1200-mesh sandpapers in turn, and after alcohol ultrasonic degreasing, it is rinsed with deionized water for use.

[0040] Example 1

[0041] The concentrated sulfuric acid was diluted to 150 g / L to obtain H2SO4 electrolyte, which was used for electrochemical test of the catalytic oxygen evolution performance of Pb-Ag alloy; the ultrasonic field cleaning instrument was used as the ultrasonic field generating device, and a low-temperature constant temperature water tank was used to provide a circulating constant temperature water flow; the Pb-Ag alloy anode was subjected to LSV test in the above-configured electrolyte, the test temperature was 25°C, the variable condition was ultrasonic field, and the test results showed that the obtained ultrasonic field was 50 mA / cm 2 The oxygen evolution overpotential of the Pb-Ag alloy anode electrode is 81 mV lower than that when no ultrasonic field is applied.

[0042] Example 2

[0043] The concentrated sulfuric acid was diluted to 150g / L to obtain H2SO4 electrolyte, which was used for electrochemical testing of the catalytic oxygen evolution performance of Pb-Ag alloy; the ultrasonic field cleaning instrument was used as an ultrasonic field generating device, and a low-temperature constant temperature water tank was used to provide a circulating constant temperature water flow. The Pb-Ag alloy anode was subjected to LSV testing in the above-configured electrolyte, the test temperature was 35°C, the variable condition was ultrasonic field, and the test results showed that the obtained ultrasonic field was 50mA / cm 2 The oxygen evolution overpotential of the Pb-Ag alloy anode electrode is 108 mV lower than that when no ultrasonic field is applied.

[0044] Example 3

[0045] The concentrated sulfuric acid was diluted to 150g / L to obtain H2SO4 electrolyte, which was used for electrochemical testing of the catalytic oxygen evolution performance of Pb-Ag alloy; the ultrasonic field cleaning instrument was used as an ultrasonic field generating device, and a low-temperature constant temperature water tank was used to provide a circulating constant temperature water flow. The Pb-Ag alloy anode was subjected to LSV testing in the above-configured electrolyte, the test temperature was 50°C, the variable condition was ultrasonic field, and the test results showed that the obtained ultrasonic field was 50mA / cm 2 The oxygen evolution overpotential of the Pb-Ag alloy anode electrode is 83 mV lower than that when no ultrasonic field is applied.

[0046] In Examples 1 to 3, when a synchronous ultrasonic field is present, the three constitute a single-factor variable experiment on temperature. The experimental results show that between 25 and 50°C, the application of a synchronous ultrasonic field can achieve a decrease in the oxygen evolution overpotential. However, the rise and fall of temperature also has a direct impact on the decrease in the oxygen evolution overpotential. The corresponding relationship is that with the increase of the electrodeposition temperature, the decrease in the oxygen evolution overpotential first increases and then decreases. At 35°C, the decrease in the oxygen evolution overpotential reaches the maximum.

[0047] Further, in order to verify the effect of the synchronous ultrasonic field in inhibiting anode corrosion, the present invention uses the synchronous ultrasonic field as a single factor variable, adopts the zinc electrowinning process of Example 2 to carry out continuous electrowinning for 5 hours, repeats 3 times, and retains the electrolyte after each electrowinning. The content of lead and silver in the above electrolyte is tested by ICP, and the results are shown in Table 1.

[0048] Table 1

[0049]

[0050] Taking the average value of three experiments, it can be seen that the ultrasonic field has little effect on the corrosion of lead, but has a significant effect on the corrosion of silver. The amount of silver dissolved under the ultrasonic field is only 0.683 mg / L, which is half of that without the ultrasonic field. This effectively proves that the ultrasonic field significantly inhibits the corrosion of silver.

[0051] Example 4

[0052] Concentrated sulfuric acid and zinc sulfate were prepared with ultrapure water to make 150 g / L H2SO4 and 50 g / L Zn 2+ The electrolyte is used for the Pb-Ag alloy simulated zinc electrowinning experiment; the ultrasonic field cleaning instrument is used as an ultrasonic field generating device, and a low-temperature constant temperature water tank is used to provide a circulating constant temperature water flow.

[0053] The Pb-Ag alloy anode was subjected to a simulated zinc electrowinning experiment in the above-configured electrolyte. The experimental temperature was 35°C, the experimental time was 5 hours, and the variable condition was an ultrasonic field. After the simulated zinc electrowinning experiment, the Pb-Ag alloy anode was retained and washed with anhydrous ethanol and ultrapure water, respectively, and then dried.

[0054] The above-mentioned Pb-Ag alloy electrode was subjected to a SEM-EDS joint test. The SEM image showed that under the action of the synchronous ultrasonic field, the PbO2 oxide layer on the anode surface grew more uniformly and the grains were finer. EDS showed that the silver content on the electrode surface was 0.4%, which was significantly higher than the silver content of 0.05% when no ultrasonic field was applied.

[0055] The present invention also conducted an LSV test on the polarity of the Pb-Ag alloy electrode at a test temperature of 35°C. The test results showed that 50 mA / cm 2 Under the action of synchronous ultrasonic field, the oxygen evolution overpotential of Pb-Ag alloy anode decreased by 115mV compared with the alloy anode without ultrasonic field.

[0056] Example 5

[0057] This example is exactly the same as Example 4, except that the cell voltage change is recorded at the beginning of electroplating. The cell voltage change curve shows that the cell voltage remains stable for 5 hours, and the cell voltage under the application of ultrasonic field is 50mV lower than the cell voltage without the application of ultrasonic field.

[0058] Furthermore, the present invention also performs SEM characterization on the cathode to obtain the growth of zinc crystals. Figure 6 It can be seen that under the action of the synchronous ultrasonic field, the obtained zinc crystals have smaller particle size, and thus based on the fine strengthening effect, the quality of the obtained zinc products is higher.

[0059] Through the related experiments of the above embodiments 1 to 5, it can be known that the synchronous ultrasonic field can effectively reduce the oxygen evolution overpotential of the anode in any link of zinc electrowinning, and can be widely used in the optimization of zinc electrowinning process. The increase in temperature will show that the decrease in the oxygen evolution overpotential increases first and then decreases. Therefore, the temperature should be strictly controlled during the zinc electrowinning process, and it should not be too high or too low. Therefore, the optimal zinc electrowinning process obtained by the optimization method of the present invention on the existing basis is: the frequency of the ultrasonic field is 40kHz, the power is 800W, the electrowinning temperature is 35°C, and the current density is 50mA / cm 2 , the time is 5h. It should be noted that the above-mentioned electrowinning process is only optimized on the basis of the original process proposed, and does not refer to the specific zinc electrowinning process in industrial production. For example, in industrial production, zinc electrowinning is usually a continuous production process, and its time length is much longer than 5h. Therefore, the process of optimizing the zinc electrowinning process conditions under different production environments by the optimization method provided by the present invention by those skilled in the art belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for optimizing a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process, characterized in that: include: Step S1, using Pb-Ag alloy as electrodes, respectively building a zinc electrowinning electrolytic cell and an LSV test electrolytic cell; Step S2, respectively energizing and electrolyzing the zinc electrolytic cell and the LSV test electrolytic cell and applying a synchronous ultrasonic field to obtain an anode LSV curve; Step S3, after the zinc electrolytic deposition is completed, the anode is recovered, the electrolytic oxide layer film of the recovered anode is retained and its LSV curve is obtained again; Step S4, repeating steps S1 to S3 to perform single factor variable optimization on zinc electrowinning process parameters to obtain the best process conditions; The zinc electrolytic cell comprises: 2+ The solution is an electrolytic solution, a Pb-Ag alloy anode, and an Al cathode; The LSV test electrolytic cell comprises: sulfuric acid electrolyte, Pb-Ag alloy as working electrode, platinum sheet electrode as auxiliary electrode, and mercurous sulfate electrode as reference electrode.

2. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The electrolytic solution includes 100-150 g / L sulfuric acid and 30-70 g / L Zn 2+ .

3. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The Pb-Ag alloy also needs to be pretreated, and the process is: the Pb-Ag alloy is polished flat with 600 mesh and 1200 mesh sandpaper in turn, and then ultrasonically degreased, cleaned and dried to obtain the alloy.

4. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The power of the synchronous ultrasonic field is 100-800W, and the frequency is 20-60kHz; the conditions of the zinc electrowinning process are: the current density is 40-60mA / cm 2 , the temperature is 20 ~ 50 ℃.

5. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The anode recovery process is as follows: the anode after zinc electrowinning is rinsed with distilled water and anhydrous ethanol for 2 to 5 times in sequence, and then vacuum dried to obtain the anode.

6. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The test process of the recovery anode LSV curve is: using a three-electrode system and 100-150 g / L sulfuric acid as an electrolyte to perform an electrocatalytic oxygen evolution test.

7. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: The variable factors for optimizing the zinc electrowinning process parameters include: electrowinning temperature, electrowinning time, ultrasonic field and current density.

8. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 1, characterized in that: Before optimizing the zinc electrowinning process parameters, it is also necessary to test the ion concentration of the zinc electrowinning electrolyte to obtain the lead and silver ion concentrations.

9. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 8, characterized in that: The zinc electrowinning process parameter optimization process is: statistically analyzing the LSV curves and ion concentrations of the zinc electrowinning electrolyte obtained under each single factor variable experiment, and establishing the correlation between the optimization effect and each variable factor through the two.

10. The optimization method of a synchronous ultrasonic field low oxygen evolution overpotential zinc electrodeposition process according to claim 9, characterized in that: The decrease in the oxygen evolution overpotential is positively correlated with the optimization effect; and the ion concentration is negatively correlated with the optimization effect.